Au → M bonds promote catalytic alkyne hydrofunctionalisation. Issue 36 (18th April 2023) - Eltester, M. Alexander; Gildenast, Hans; Rabatinová, Kristína; Pütz, Christopher; Cremer, Christopher; Lanzerath, Patrick; Schroers, Julian P.; Tauchert, Michael E.
Abstract : Coordination of metalloligands Cu +, Ag + and Zn 2+ controls the Lewis acidity of heterobimetallic Au I catalysts thus promoting alkyne hydrofunctionalisation. Abstract : The impact of metalloligands on Au catalysed alkyne hydrofunctionalisation is studied. Ambiphilic PMP-type ligands (M = Cu I, Ag I, Zn II ) stabilise Au → M bonds including unprecedented Au I → Zn II interactions. The Lewis acidity of Au increases in the order Cu I < Ag I < Zn II promoting catalytic cycloisomerisation of propargylamide 14. Au/Zn complex 8 is an excellent catalyst for alkyne hydroamination.